The Subprime Crisis and Its Effects on the Efficiency of the Chilean Banking Sector [a Crise Do Subprime E Seus Efeitos Sobre a Eficiência Do Setor Bancário Chileno] [la Crisis Subprime y Sus Efectos en la Eficiencia del Sector Bancario Chileno] - Gonzalez-Cid, M (Universidad Externado de Colombia, 2019)
The objective of the research is to measure the effects of the subprime crisis on the production of efficiency and on the technical efficiency of the banking industry in Chile. For this, stochastic frontier production function methodology was used for a balanced data panel that collected information from 14 banks operating in Chilean territory for the period 2004-2015. The main results of the investigation indicate that during the crisis period, the production of efficiency and technical efficiency of the banking industry is lower, finding more important differences with respect to the period after the crisis. © 2019, Revista de Economia Institucional. All rights reserved.